2019
DOI: 10.1038/s41598-019-46279-5
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian CTLH complex is an E3 ubiquitin ligase that targets its subunit muskelin for degradation

Abstract: The multi-subunit C-terminal to LisH (CTLH) complex is the mammalian homologue of the yeast Gid E3 ubiquitin ligase complex. In this study, we investigated the human CTLH complex and characterized its E3 ligase activity. We confirm that the complex immunoprecipitated from human cells comprises RanBPM, ARMC8 α/β, muskelin, WDR26, GID4 and the RING domain proteins RMND5A and MAEA. We find that loss of expression of individual subunits compromises the stability of other complex members and that MAEA and RMND5A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(98 citation statements)
references
References 58 publications
4
93
1
Order By: Relevance
“…Nonetheless, so far the CTLH complex appears simpler than the human and yeast complexes. We were unable to identify orthologs of GID4 and GID5, which are seen in the human and yeast versions (Lampert et al, 2018;Maitland et al, 2019;Santt et al, 2008). Similarly, although WDR26 is important in the human complex and we identified a Drosophila ortholog (CG7611), we found no evidence of its association with ME31B or requirement for ME31B degradation.…”
Section: Discussioncontrasting
confidence: 62%
“…Nonetheless, so far the CTLH complex appears simpler than the human and yeast complexes. We were unable to identify orthologs of GID4 and GID5, which are seen in the human and yeast versions (Lampert et al, 2018;Maitland et al, 2019;Santt et al, 2008). Similarly, although WDR26 is important in the human complex and we identified a Drosophila ortholog (CG7611), we found no evidence of its association with ME31B or requirement for ME31B degradation.…”
Section: Discussioncontrasting
confidence: 62%
“…Our previous report suggests that the GID complex is involved in the ubiquitination of β-Catenin and is independent of the Wnt signalling pathway 16 . Among the components of the GID complex, RMND5A and MAEA (mammalian homologues of yeast GID2 and GID9, respectively) encode E3 ubiquitin ligases [33][34][35] . We confirmed that RMND5A and MAEA ubiquitinated β-Catenin directly ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Qiao et al (46) employed cryoelectron microscopy and other methods to characterize the entire GID Ub ligase, revealing its overall shape and also, in particular, specific interactions between its N-recognin subunit GID4 and the rest of GID. In mammals, the GID Ub ligase (it is also called CTLH) functions in primary cilia, in cell proliferation, and in other processes (96,(102)(103)(104)(105)(106)(107)(108)(109)(110).…”
Section: Significancementioning
confidence: 99%